Japan’s Digital Disaster Diplomacy: Evaluating the Safety Tips Application in Protecting Indonesian Citizens - Ammar, Nabila Maulida; Jatmika, Sidik (Universitas Muhammadiyah Yogyakarta, 2025)
This research examined the application of Safety Tips for Disaster as a digital diplomacy tool employed by Japan to ensure the safety of Indonesian citizens (WNI) during natural disasters. This research utilized qualitative studies to analyze official documents related to the Safety Tips application, including publications from the Japan Tourism Agency (JNTO), journal articles, relevant disaster response policies, and interviews with relevant representatives. Findings highlight the application’s effectiveness in delivering timely information and early warnings, facilitating coordination between Japanese authorities and Indonesian representatives, including the Embassy in Tokyo and the Consulate General in Osaka, for crisis management. Although digital diplomacy has been widely analyzed in the context of public diplomacy and social media, its application in disaster management remains underexplored. The Safety Tips for Disaster application emerged as a model that Indonesia could adopt to strengthen its digital diplomacy strategies, thereby improving the safety and readiness of its citizens during natural disasters in Japan.